2008
DOI: 10.1016/j.etap.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

2-(4′-chlorophenyl)-1,4-benzoquinone increases the frequency of micronuclei and shortens telomeres

Abstract: The toxicity of polychlorinated biphenyls (PCBs) has been attributed widely to receptor-mediated effects, buttressed by the popularity of the Toxic Equivalency Factor. We propose that a crucial toxic mechanism of lower-chlorinated PCBs is their enzymatic biotransformation to electrophiles, including quinoid metabolites, that bind intracellular sulfhydryl groups, such as those found in microtubulin and enzymes like telomerase. To test this hypothesis, we have examined micronuclei induction, cell cycle, and telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 22 publications
1
39
3
Order By: Relevance
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro , immortalized human skin keratinocytes, hamster lung fibroblasts, immortalized lymphocytes, or human promyelocytic leukemia cells exposed to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ), have shortened telomeres (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Conversely, PCB 138 and PCB 153 upregulate c- myc in vitro (Ghosh et al, 2007; Gribaldo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is probably due to the influence of exposure on genes involved in the telomere length maintenance (32). Correlation of age and telomere length in our study suggested a possible influence of the widespread environmental and occupational ha zards ex posure on ageing acceleration (33)(34)(35), through shortening the telomere length.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have reported that chronic dietary administration of BHA caused DNA damage [3] and even induced papilloma and carcinoma formation in forestomach of rats, mice and hamsters [4,5]. Moreover, BHA has been shown to act as a tumor initiator or promoter in a variety of tissues and organs, and its quinone-forming metabolites which are highly reactive molecules with binding to biological macromolecules [6] can also induce chromosomal loss or chromosomal breakage [7]. Because of the widespread uses of BHA, it is necessary to critically evaluate the safety of this antioxidant.…”
Section: Introductionmentioning
confidence: 99%